2021
DOI: 10.1155/2021/4989282
|View full text |Cite
|
Sign up to set email alerts
|

Dance/Movement Therapy as an Intervention in Breast Cancer Patients: A Systematic Review

Abstract: Aim. In this paper, we systematically review the evidence looking at the effect of dance/movement therapy (DMT) and mental health outcomes and quality of life in breast cancer patients. Method. The literature search was done with the databases PubMed (MEDLINE), EBSCO, and Cochrane Central by using the following search words: “dancing/dance/movement therapy,” “breast cancer/neoplasms/carcinoma/tumour” or “mammary cancer,” “mental health,” and “quality of life.” Ninety-four articles were found. Only empirical in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Of these five studies, three [37,39,40] observed statistically significant improvements, and another study [33] only observed an improvement in the Physical Component Summary. Similar results are found in several systematic reviews such as that by Ma et al [60] in which they explored the beneficial effects of rhythmic movement interventions on quality of life, but only in cognitively healthy older adults over the age of 60 years; despite these results, these authors recommended further studies with larger population samples, where the gender ratio is balanced, and follow-up is conducted over a prolonged period; the review by Fatkulina et al [61] reported an improved quality of life in women diagnosed with breast cancer after dance/movement therapy; and the review by Lötzke et al [62] revealed the positive effects on quality of life after an Argentine tango-based intervention in patients with Parkinson's disease. In contrast to the previously mentioned results, this systematic review and meta-analysis found one study [38] that did not report positive changes in quality of life.…”
Section: Discussionsupporting
confidence: 61%
“…Of these five studies, three [37,39,40] observed statistically significant improvements, and another study [33] only observed an improvement in the Physical Component Summary. Similar results are found in several systematic reviews such as that by Ma et al [60] in which they explored the beneficial effects of rhythmic movement interventions on quality of life, but only in cognitively healthy older adults over the age of 60 years; despite these results, these authors recommended further studies with larger population samples, where the gender ratio is balanced, and follow-up is conducted over a prolonged period; the review by Fatkulina et al [61] reported an improved quality of life in women diagnosed with breast cancer after dance/movement therapy; and the review by Lötzke et al [62] revealed the positive effects on quality of life after an Argentine tango-based intervention in patients with Parkinson's disease. In contrast to the previously mentioned results, this systematic review and meta-analysis found one study [38] that did not report positive changes in quality of life.…”
Section: Discussionsupporting
confidence: 61%
“…Generally, mindfulness and Yoga are feasible and efficient ET [ 31 ] and they must be included in all ET. To work on mental health, dance or movement therapy could be successfully considered as a complementary therapy [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…The recommended forms of physical activity after BC removal include Nordic walking [ 16 ], dance therapy [ 17 ], music therapy, virtual reality therapy [ 18 ], yoga [ 19 ], Tai Chi [ 20 ], reflexology as well as aquatic physical therapy [ 21 ]. Women who are involved in vigorous physical activity minimize the risk of BC up to 30–40% [ 22 ].…”
Section: Discussionmentioning
confidence: 99%